A laboratory stress-test of bid, double and offer auctions - Morten Søberg (Statistics Norway, Research Department, 2002)
This paper reports on the empirical properties of the bid auction (buyers propose prices), offer auction (sellers suggest prices) and double auction (both buyers and seller initiate price quotes). These trading institutions are stress-tested using a nonstationary monopolistic market environment in which the buyers' demand schedule and the single seller's supply curve shift unpredictably between trading periods. The principal result is threefold. First, double-auction prices tend to be greater than offer-auction prices which again tend to be greater than bid-auction prices. Second, the listed ranking reflects tendencies only. The laboratory data do not support statistically significant behavioral differences between the three auctions. Third, trading is highly efficient regardless of auction type.
Keywords: D44; C90; 330; Sequential auctions; experimental economics.